Sistem Informasi Tempat Bersejarah di Jawa Tengah Berbasis Website - Aji, Bayu Kusuma; , Dedi Gunawan, S.T., M.Sc (2016)
Historic sites in Central Java increasingly crowded domestic and non- domestic, is because many historic sites in Central Java and tourism potentials at disposal. However, due to the limitations of existing information makes some tourists lack of information about the history of the place that will be addressed. Therefore it is very important to create a system that is able to provide information about tourist attractions, especially in the region of Central Java. This study purposed to make the information system Web-based historical places. The methodology in making this system is the waterfall methodology. This application is built using the framework code Igniter PHP programming language and MySQL as the database. The web application information system is able to provide information and an overview of historic sites in Central Java. The results of application testing that has been done is good, easy to use application and received good response from the user.